Pertanggungjawaban Pidana dan Etik terhadap Penyalahgunaan Narkotika oleh Anggota Kepolisian - Rahmawati, Yenny; Kartika, Tantri (PT Elaborium Elevasi Indonesia, 2025)
Drug abuse by police officers not only raises legal issues, but also ethical issues in the police profession. In this case, criminal and ethical liability are two interrelated aspects. Criminal liability relates to legal actions that must be taken against police officers who are proven guilty of drug abuse, while ethical liability relates to violations of the police code of ethics that reflect the morals and integrity of the profession. The formulation of the problem is 1) How are the legal regulations related to drug abuse by police officers in Indonesia? 2) How are the criminal and ethical liabilities for police officers involved in drug cases? The approach method used in this legal research is to use the normative legal approach method. The results of the research are legal regulations related to criminal acts committed by members of the police, namely regulated in several regulations, Law Number 2 of 2002 concerning the Republic of Indonesia Police, Law Number 35 of 2009 concerning Narcotics, Law Number 36 of 2009 concerning Health and criminal and ethical responsibility for police members involved in narcotics cases, Criminal sanctions that can be given in the form of imprisonment and fines according to the crime committed.